Loss of GSTO2 contributes to cell growth and mitochondria function via the p38 signaling in lung squamous cell carcinoma - Sumiya, Ryusuke; Terayama, Masayoshi; Hagiwara, Teruki; Nakata, Kazuaki; Sekihara, Keigo; Nagasaka, Satoshi; Miyazaki, Hideki; Igari, Toru; Yamada, Kazuhiko; Kawamura, Yuki I. (Cancer science, 2022)
Glutathione S‐transferase omega 2 (GSTO2) lacks any appreciable GST activity, but it exhibits thioltransferase activity. The significance of GSTO2 in lung function has been reported; however, the precise expression and molecular function of GSTO2 in the lungs remain unclear. In the present study, we found that GSTO2 is expressed in airway basal cells, non–ciliated, columnar Clara cells, and type II alveolar cells, which have self‐renewal capacity in the lungs. Contrastingly, no GSTO2 expression was observed in 94 lung squamous cell carcinoma (LSCC) samples. When human LSCC cell lines were treated with 5‐aza‐2′‐deoxycytidine, a DNA‐methyltransferase inhibitor, GSTO2 transcription was induced, suggesting that aberrant GSTO2 hypermethylation in LSCC is the cause of its downregulation. Forced GSTO2 expression in LSCC cell lines inhibited cell growth and colony formation in vitro. In a subcutaneous xenograft model, GSTO2‐transfected cells formed smaller tumors in nude mice than mock‐transfected cells. Upon intravenous injection into nude mice, the incidence of liver metastasis was lower in mice injected with GSTO2‐transfected cells than in those injected with mock‐transfected cells. In addition, GSTO2 induction suppressed the expression of β‐catenin and the oxygen consumption rate, but it did not affect the extracellular acidification rate. Furthermore, GSTO2‐transfected cells displayed lower mitochondrial membrane potential than mock‐transfected cells. When GSTO2‐transfected cells were treated with a p38 inhibitor, β‐catenin expression and mitochondrial membrane potential were recovered. Our study indicated that the loss of GSTO2 via DNA hypermethylation contributes to the growth and progression of LSCC, probably by modulating cancer metabolism via the p38/β‐catenin signaling pathway. Glutathione S‐transferase omega 2 (GSTO2) is expressed in the stem cells of the bronchial and alveolar epithelium. Loss of GSTO2 might contribute to lung squamous cell carcinoma growth by modulating cancer metabolism via the p38/β‐catenin signaling pathway.